2019
DOI: 10.20411/pai.v4i1.271
|View full text |Cite
|
Sign up to set email alerts
|

CD32-RNA Co-localizes with HIV-RNA in CD3+ Cells Found within Gut Tissues from Viremic and ART-Suppressed Individuals

Abstract: Background: Identifying biomarkers for cells harboring replication-competent HIV is a major research priority. Recently, there have been mixed reports addressing the possibility that CD32-expressing T-cells are enriched for HIV. There is growing evidence that CD32 expression increases with cellular activation that may be related to, but not necessarily specific for, infection with HIV.  However, the relationship of CD32 expression to HIV-infection in subtypes of tissue-resident leukocytes is unclear.  Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
4
18
1
Order By: Relevance
“…These RNA in situ hybridization (ISH) experiments showing the co-expression of CD32a RNA and HIV RNA in lymphoid tissue support the notion that CD32a is associated with transcriptionally active tissue reservoirs. Similar results were recently obtained by Vásquez et al in the gut tissue (114). By using ISH-based methods, they demonstrated co-expression of HIV and CD32a mRNA, with most of the CD3 + CD32 + cells in the gut co-expressing HIV RNA.…”
Section: Cd32asupporting
confidence: 92%
“…These RNA in situ hybridization (ISH) experiments showing the co-expression of CD32a RNA and HIV RNA in lymphoid tissue support the notion that CD32a is associated with transcriptionally active tissue reservoirs. Similar results were recently obtained by Vásquez et al in the gut tissue (114). By using ISH-based methods, they demonstrated co-expression of HIV and CD32a mRNA, with most of the CD3 + CD32 + cells in the gut co-expressing HIV RNA.…”
Section: Cd32asupporting
confidence: 92%
“…1b and 1c). These data together with recent publications demonstrating that CD32–RNA correlates with HIV transcriptional activity in T cells from the gut 13 , and from lymph nodes 10 , not only confirms their existence in human tissues, but also raises interest on defining their nature.
Fig. 2CCR5 + CD4 + T RM protein expression signature in cervix.
…”
Section: Resultssupporting
confidence: 75%
“…Interestingly, we detected a small subset of cervical CD4 + CCR5 + T RM that readily expressed CD32, a marker originally associated to HIV-latently infected cells 9 , which was later linked to transcriptionally active infected cells 1013 . We observed that the fraction of T RM expressing CD32 was enriched for most of the molecules investigated, many of them associated to HIV susceptibility.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations